HUBUNGAN KOORDINASI MATA TANGAN, KEKUATAN LENGAN DAN MOTIVASI BERPRESTASI DENGAN KETEPATAN FOREHAND DALAM TENIS MEJA - Pratama, Sandi Achmad; Budiman, Budiman (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2017)
[Title: Relationship of Hand Eye Coordination, Arm Strength and Achievement Motivation with Forehand Accuracy in Table Tennis] This study aims to determine the relationship between: 1) hand eye coordination with precision forehand; 2) arm strength with forehand precision; 3) achievement motivation with precision forehand; 4) hand eye coordination, arm strength, and achievement motivation together with forehand precision. This research uses quantitative approach, survey method and correlation technique. Research subjects are athletes at pandusiwi club in dompu district as many as 30 athletes. Data analysis using correlation and regression with SPSS 20. The results showed that there is a significant relationship between: 1) hand eye coordination with precision forehand; 2) arm strength with forehand precision; 3) achievement motivation with precision forehand; 4) hand eye coordination, arm strength, and achievement motivation together with forehand precision.